Hubungan Pengetahuan tentang Osteoporosis dengan Perilaku Pencegahan Osteoporosis pada Wanita Premenopause di Desa Cicantayan Wilayah Kerja Puskesmas Cicantayan Kabupaten Sukabumi - Herlina Lidiyawati; Sri Nur Oktaviani (Lentera : Jurnal Ilmiah Kesehatan dan Keperawatan, 2021)
Osteoporosis is a condition in which the loss of bone mass is at an alarming point, so that the bones lose their flexibility and strength. This study aims to determine the relationship between knowledge about osteoporosis and prevention of osteoporosis in premenopausal women in Cicantayan Village, Cicantayan Community Health Center, Sukabumi Regency. Osteoporosis is bone loss due to loss of mass in the bone which can increase the risk of fractures. Knowledge is a result of curiosity from the results of sensing. Attitude is a response to a stimulus. This type of research is correlational with a Cross Sectional approach. The population of this study were all premenopausal women 41-50 years old with a total of 469 people. The research sample amounted to 82 people taken by cluster random sampling. Data analysis using chi square. The results showed that knowledge about osteoporosis was good with behavior to prevent as many as 23 respondents (50.0 %). The chi square statistical test shows that the significance value of p = 0.027 < a (0.05) so that H1 is accepted. The conclusion of this study is that there is a relationship between knowledge about osteoporosis and osteoporosis prevention behavior in premenopausal women in Cicantayan Village, Cicantayan Health Center Work Area, Sukabumi Regency.